Residential distance at birth from overhead high-voltage powerlines: childhood cancer risk in Britain 1962–2008 - Bunch, K J (Nature Publishing Group, 2014)
BACKGROUND: We extend our previous study of childhood leukaemia and proximity to high-voltage powerlines by including more recent data and cases and controls from Scotland, by considering 132-kV powerlines as well as 275 and 400 kV and by looking at greater distances from the powerlines. METHODS: Case–control study using 53 515 children from the National Registry of Childhood Tumours 1962–2008, matched controls, and calculated distances of mother's address at child's birth to powerlines at 132, 275, and 400 kV in England, Wales and Scotland. RESULTS: Our previous finding of an excess risk for leukaemia at distances out to 600 m declines over time. Relative risk and 95% confidence interval for leukaemia, 0–199 m compared with>1000 m, all voltages: 1960s 4.50 (0.97–20.83), 2000s 0.71 (0.49–1.03), aggregate over whole period 1.12 (0.90–1.38). Increased risk, albeit less strong, may also be present for 132-kV lines. Increased risk does not extend beyond 600 m for lines of any voltage. CONCLUSIONS: A risk declining over time is unlikely to arise from any physical effect of the powerlines and is more likely to be the result of changing population characteristics among those living near powerlines.